2021
DOI: 10.1002/jmv.26855
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis value of SARS‐CoV‐2 antigen/antibody combined testing using rapid diagnostic tests at hospital admission

Abstract: The implementation of rapid diagnostic tests (RDTs) may enhance the efficiency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing, as RDTs are widely accessible and easy to use. The aim of this study was to evaluate the performance of a diagnosis strategy based on a combination of antigen and immunoglobulin M (IgM) or immunoglobulin G (IgG) serological RDTs. Plasma and nasopharyngeal samples were collected between 14 March and 11 April 2020 at hospital admission from 45 patients with rever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…The selection of RDT products covered the different antigens used and had various regulatory approvals. Some of them were produced by reputable manufacturers and had been successfully validated in peer-reviewed studies [ 6 , 21 , 25 , 34 , 63 , 64 , 65 , 66 ] and approved by regulatory authorities (FDA EUA) and independent actors such as FIND [ 2 ]. In addition, the laboratory workflow was highly standardized and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of RDT products covered the different antigens used and had various regulatory approvals. Some of them were produced by reputable manufacturers and had been successfully validated in peer-reviewed studies [ 6 , 21 , 25 , 34 , 63 , 64 , 65 , 66 ] and approved by regulatory authorities (FDA EUA) and independent actors such as FIND [ 2 ]. In addition, the laboratory workflow was highly standardized and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…15 studies compared the clinical performance of one RAT against RT-PCR: six studies compared the Roche/SDB; 12-17 six compared the Abbott; [18][19][20][21][22][23] and three compared the Coris RAT. [24][25][26] All studies provided descriptions of the study populations, regarding mean age and gender distribution (data not shown), as well as symptoms, prevalence rates, and Ct of the RT-PCR-positive samples. Prevalence rate -here meaning the number of RT-PCR-positive samples within the overall study population -varied between 1.9-100%.…”
Section: Study Population Characteristicsmentioning
confidence: 99%
“…Developments include immunological methods, such as Enzyme Linked Immunosorbent Assays (ELI-SAs), chemiluminescence immunoassays (CLIAs), lateral ow immunoassays (LFIAs), and multiple others. [3][4][5][6][7] Recently, the development of clustered regularly interspaced short palindromic repeats (CRISPR)-based diagnostics has been used to detect the SARS-CoV-2 virus. 8,9 This method is very promising but is still in an early stage.…”
Section: Introductionmentioning
confidence: 99%